Sociolinguistic determinants of heritage language maintenance and second language acquisition in bilingual immigrant speakers - Banasiak, Ilona; Olpińska-Szkiełko, Magdalena (Glottodidactica, 2020)
The objective of the study was to scrutinise the determinants of heritage language maintenance and second language acquisition in immigrant speakers and assess their significance and weight. Over one hundred cases of bilingual speakers with Polish as L1 (heritage language; Polish speakers abroad) and as L2 (national language; immigrant learners of Polish in Poland) were investigated in order to better understand the linguistic changes and multilingual practices involved in the process of relocating to another country. The cases underwent quantitative and qualitative analysis. The results revealed that in most cases bilinguals are at a high risk of losing their L1, and L2 becomes their dominant language. With the dominance of L2, identification with the culture of the country of residence also increases in bilinguals. Formal instruction in L1 proves to be the most important factor in heritage language maintenance, and the preservation of a sense of identification with the heritage culture. An important role in L1 and also L2 development is played by parental support and their actions.